A structural perspective on the enzymes that convert dTDP-d-glucose into dTDP-l-rhamnose. (1st June 2003) - Dong, C.; Beis, K.; Giraud, M.-F.; Blankenfeldt, W.; Allard, S.; Major, L.L.; Kerr, I.D.; Whitfield, C.; Naismith, J.H.
Abstract : Bacteria have a rich collection of biochemical pathways for the synthesis of complex metabolites. These conversions often involve chemical reactions that are hard to reproduce in the laboratory. An area of considerable interest is in the manipulation and synthesis of carbohydrates. In contrast with amino acids, carbohydrates are densely functionalized (each carbon atom is attached to at least one heteroatom) and this holds out the prospect of discovering novel enzyme mechanisms. The results from the study of the biosynthetic dTDP-l -rhamnose pathway are discussed. dTDP-l -rhamnose is a key intermediate in many pathogenic bacteria, as it is the donor for l -rhamnose, which is found in the cell wall of important human pathogens, such as Mycobacteria tuberculosis and Salmonella typhimurium . All four enzymes have been structurally characterized; in particular, the acquisition of structural data on substrate complexes was extremely useful. The structural data have guided site-directed-mutagenesis studies that have been used to test mechanistic hypotheses. The results shed light on three classes of enzyme mechanism: nucleotide condensation, short-chain dehydrogenase activity and epimerization.